Mammal diversity in the middle basin of the river Tambopata, Puno, Peru - Pacheco, Víctor (2011)
This study documents the mammalian diversity in the Tambopata River middle basin, one of the most important information gaps in Peru. Five sites were evaluated in Puno (San Fermín 850 m, Curva Alegre 950 m, Challohuma 1200 m, Yanahuaya 1600 m, and Yanacocha 1985 m). The trapping effort was 7072 trap-nights and 201 mistnet-nights. 76 species were recorded in the study area, including 16 species under some conservation’s category. Bats and rodents were the most diverse orders (67.5%). The diversity indices of Shannon-Wiener and Simpson for small mammals show a moderate and mild negative correlation with elevation, respectively. Meanwhile the altitude is negatively correlated with the relative abundance (RA) of bats, and positively with the RA of non-volant mammals. The marsupials Marmosa (Micoureus) demerarae, Marmosops bishopi and Marmosops impavidus; the rodent Neacomys musseri, and bats Platyrrhinus albericoi, P. masu, P. nigellus, Eumops auripendulus and Cormura brevirostris are first records for the department of Puno. Akodon baliolus and Oxymycterus juliacae are considered valid species. The species Sturnira lilium and Akodon baliolus were those with the highest RA. Our records, added to published and unpublished data, indicate that the Río Tambopata watershed is habitat of 141 species of mammals. Finally, we recommend the extension of the southern part of the buffer zone of the PNBS to include the montane forests of Yanacocha, to protect the unique middleelevation fauna of the Río Tambopata watershed.